FENOMENA PERUBAHAN IKLIM DALAM TINJAUAN DEEP ECOLOGY ARNE NAESS DAN RELEVANSINYA DENGAN PENANGANAN PERUBAHAN IKLIM - , DATU HENDRAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Climate change is one of the environmental issues that have an impact so large.it can be referred to as a global environmental disaster. Climate change is a problem caused by human activities, which tend to be anthropocentric. Greenhouse gases that keep the Earth warm has risen to a very high level and makes the temperature of the earth increase every year. Increasing the temperature of the earth poses a potential danger to all living beings on this planet with climate change disaster. Naessâs Deep Ecology trying to change the way anthropocentrism by offering an ecosentrism perspective. The purposes of the research are to get understanding about caused of climate change, to analyze climate change with Deep Ecology Theory, and to find Deep Ecology relevance in climate change convention and climate change handling in Indonesia This research is a library research, with main source book âSepuluh Tahun Perjalanan Konvensi Perubahan Iklimâ by Daniel Murdiyarso and âKrisis dan Bencana Lingkungan Hidup Globalâ by Sonny Keraf.This research using philosophical hermeneutics method as a tool to analyze data related with the subsequent theme. The methodical elements used in this research are: description, historical continuity, interpretations, internal coherence, and holistic. The results achieved in this research are: 1) anthropocentrism perspective which views human beings as the center of the universe and the only source of value caused many environmental problems, including climate change. Environmental problems occur because humans treat nature with exploitative manner and donât have respect to the life support aspect 2) Naessâs Deep Ecology Theory who gave much attention to environmental issues and sustainable living can be used as an alternative world view to improving human relations with the environment. Naessâs ecological principles may become the basis to finding the right solution fora lot of environmental problems, including climate change. 3) Deep Ecology can used to be a foundation in efforts to address climate change in the climate change convention and the establishment of law in Indonesia. Ecosentrism awareness in Deep Ecology would be a good basis for the implementation of policies addressing climate change. Environment laws in Indonesia will be implemented well if government and civil society have Deep Ecology awareness.